Analisis Perkembangan Bisnis Ritel Di Indonesia - Dea Meliana; Junita Riswati; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Retail business in Indonesia continues to grow rapidly in line with the increasing middle class, urbanization, and changing lifestyles. Modern retail, which includes hypermarkets, supermarkets, department stores, and minimarkets, has expanded to smaller cities. This phenomenon provides economic benefits, such as boosting domestic consumption, creating job opportunities, and increasing tax revenues. However, unhealthy competition, both between modern and traditional markets and among modern market players, remains a major challenge. With appropriate regulations, such as restrictions on distance, operating hours, and spatial planning, modern retail businesses can thrive without compromising the sustainability of traditional markets. This study discusses the development of retail business, supporting factors, and forces influencing competition in this industry.